Operational Analysis Of Strategic Plan Based On The Perspective Of Balanced Scorecard Performance Of Hospital Employees At Royal Prima Hospital Medan - Khairinnisa Hasibuan; Ermi Girsang; Sri Lestari Ramadhani (International Journal of Health and Pharmaceutical (IJHP), 2022)
Performance appraisal using the Balanced Scorecard method measures a hospital’s performance comprehensively from both the financial and non-financial sectors. As a health service company must have a comprehensive, coherent, balanced and measurable performance appraisal system. This study aims to analyze, test, and measure the performance of the hospital by using The Balance Scorecard case study at Royal Prima Hospital Medan. According to the balanced scorecard, the research problem was how about the performance of Royal Prima Hospital Medan in the period of 2018-2020. The assessment was done from four perspectives: financial perspective, customer perspective, internal business perspective, and growth and learning perspective. The research used mixed methods, a research step by combining two types of research, qualitative and quantitative research. The data were gathered by conducting a documentary study on financial statements, medical records, and personnel records. Primary data were obtained from the interviews with the management and distributing questionnaires to customers and employees in the hospital. The results of the research showed that the performance of the financial perspective on economic ratios is not yet economical, while the efficient and effectiveness ratios are very good, the financial performance of Royal Prima Hospital Medan has been very effective and efficient from 2018 to 2020. The Hospital performance from the customer perspective in the period of 2018-2020 for the percentage of customer retention is still not good, customer acquisition is very good and customer satisfaction is quite good. The performance of internal business perspective in the period 2018-2020 was not good in which the percentage of BOR, BTO, and TOI were not in accordance with the standard of the Ministry of Health. The performance of the percentage of growth and learning at Royal Prima Hospital Medan perspective in the period of 2018 - 2020 shows a fairly good percentage.